Lithium zirconium aluminosilicate glass, tempered glass, its manufacturing method and display part

By using lithium zirconium aluminosilicate glass of specific components and undergoing chemical reinforcement treatment, a compressive stress layer with a depth of more than 100 μm is formed, which solves the problem of insufficient mechanical strength of the existing glass and achieves higher mechanical strength and impact endurance.

JP7654646B2Active Publication Date: 2025-04-01QINGYUAN CSG NEW ENERGY SAVING MATERIALS CO LTD +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2022520722
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-10-10
Filing Date
2019-12-31
Publication Date
2025-04-01
Estimated Expiration
2039-12-31

AI Technical Summary

Technical Problem

Existing glass is insufficient mechanical strength when protecting mobile devices and cannot effectively withstand the impact and fall of the equipment.

Method used

Lithium zirconium aluminosilicate glass containing specific components is used to obtain high-strength heat-treated glass through chemical reinforcement treatment. The composition of the glass includes 50% to 72% SiO2, 10% to 27% Al2O3, 0.1% to 10.0% B2O3, 2% to 10% Li2O, 4% to 15% Na2O, 0.1% to 5.0% ZrO2, and a compressive stress layer with a depth of more than 100 μm is formed through a specific heat treatment process.

Benefits of technology

The mechanical strength and impact endurance of the glass are significantly improved, and can effectively protect mobile devices from damage from drops and other external shocks.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007654646000006
    Figure 0007654646000006
  • Figure 0007654646000007
    Figure 0007654646000007
  • Figure 0007654646000001
    Figure 0007654646000001
Patent Text Reader

Abstract

The lithium zirconium aluminosilicate glass contains, by mass, 50% to 72% SiO2, 10% to 27% Al2O3, 0.1% to 10.0% B2O3, 2% to 10% Li2O, 4% to 15% Na2O, 0.1% to 5.0% ZrO2, and 0 to 4% K2O, the total mass of Li2O, Na2O, and K2O is 9% or more, and the ratio of the mass of Li2O to the total mass of Li2O, Na2O, and K2O is (0.22 to 0.48:1).
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of glass, and in particular to lithium zirconium aluminosilicate glass, tempered glass, its manufacturing method and display components. [Background technology]

[0002] Thin glass is a component used to protect the display panel of a display component without affecting the display effect. Many display components are known, such as mobile phones, personal digital assistants (PDAs), digital cameras, and flat panel displays (FPDs). In recent years, the demand for mechanical strength of glass has increased with the thinning and high functionality of display components such as mobile phones and PDAs. Therefore, tempered glass is generally obtained by further chemical strengthening of thin glass. Such tempered glass can be chemically strengthened by ion exchange treatment to exchange sodium ions and lithium ions on the glass surface with potassium ions or sodium ions in ion exchange salts to form a compressive stress layer on the glass surface.

[0003] In the conventional glass cover plate market, the main products are boron aluminosilicate glass and lithium boron aluminosilicate glass, such as Corning Gorilla Glass, NEG T2X-1, Asahi Glass Dragontrail Glass, China Xuhong Panda Glass, and China Nanbo KK3 Glass. However, conventional glass does not have a high enough strength, so it cannot provide sufficient protection when used as a protective glass for mobile devices. Summary of the Invention [Problem to be solved by the invention]

[0004] Thus, there is a need to provide stronger lithium zirconium aluminosilicate glasses.

[0005] Additionally, tempered glass, methods for making tempered glass, and display components are provided. [Means for solving the problem]

[0006] A lithium zirconium aluminosilicate glass comprising, by weight, 50%~72% SiO2, 10% to 27% Al2O3, 0.1%~10.0% B2O3, 2% to 10% LiO, 4% to 15% Na2O, 0.1% to 5.0% ZrO2, and Contains 0-4% K2O, A lithium zirconium aluminosilicate glass, in which the sum of the masses of Li2O, Na2O, and K2O is 9% or more, and the ratio of the mass of Li2O to the sum of the masses of Li2O, Na2O, and K2O is (0.22-0.48):1.

[0007] A tempered glass obtained by chemical tempering the lithium zirconium aluminosilicate glass.

[0008] A method for producing tempered glass, comprising the steps of first tempering the lithium zirconium aluminosilicate glass in a molten mixture of NaNO3 and KNO3 in a mass ratio of 2:8 to 8:2 at a temperature of 390°C to 420°C for 2 to 6 hours, and then tempering the glass in a molten mixture of NaNO3 and KNO3 in a mass ratio of 0.1:99.9 to 15:85 at a temperature of 380°C to 400°C for 2 to 4 hours, to obtain tempered glass.

[0009] A display component comprising the lithium zirconium aluminosilicate glass, or the tempered glass, or tempered glass produced by the method for producing tempered glass.

[0010] The details of one or more embodiments of the invention are set forth in the accompanying drawings and the description which follows. Other features, objects and advantages of the invention will become apparent from the description, the accompanying drawings, and the patent. [Brief description of the drawings]

[0011] [Figure 1] FIG. 1 is a process flow diagram of a method for making lithium zirconium aluminosilicate glass according to one embodiment. [Diagram 2] FIG. 2 is a process flow diagram of a method for producing tempered glass according to one embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] In the following, in order to facilitate understanding of the present invention, the present invention will be described more completely with reference to specific embodiments. The specific embodiments show preferred examples of the present invention. However, the present invention may be realized in many different forms and is not limited to the examples set forth herein. On the other hand, the purpose of giving these examples is to provide a more thorough and complete understanding of the present disclosure.

[0013] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which the present invention belongs. The terms used in the present specification are only for describing specific examples and are not intended to limit the present invention.

[0014] The lithium zirconium aluminosilicate glass according to one embodiment comprises, by weight, 50%~72% SiO2, 10% to 27% Al2O3, 0.1%~10.0% B2O3, 2% to 10% LiO, 4% to 15% Na2O, 0.1% to 5.0% ZrO2, and Contains 0-4% K2O, The sum of the masses of Li2O, Na2O, and K2O is 9% or more, the sum of the masses of ZrO2 and Al2O3 is more than 10%, and the ratio of the mass of Li2O to the sum of the masses of Li2O, Na2O, and K2O is (0.22-0.48:1).

[0015] In one embodiment, the lithium zirconium aluminosilicate glass further comprises at least one of MgO, CaO, SrO, ZnO, and TiO2. Specifically, the mass percentage of MgO is 6% or less, the mass percentage of CaO is 4% or less, the mass percentage of SrO is 4% or less, the mass percentage of ZnO is 4% or less, and the mass percentage of TiO2 is 2% or less. Furthermore, the mass percentage of MgO is 4% or less, the mass percentage of CaO is 2% or less, the mass percentage of SrO is 2% or less, the mass percentage of ZnO is 2% or less, and the mass percentage of TiO2 is 1% or less.

[0016] Furthermore, the lithium zirconium aluminosilicate glass further comprises at least one of MgO, ZnO, and TiO2, wherein the mass percentage of MgO is less than or equal to 2%, the mass percentage of ZnO is less than or equal to 2%, and the mass percentage of TiO2 is less than or equal to 1%.

[0017] In one embodiment, the lithium zirconium aluminosilicate glass further comprises, by mass percentage, 1% or less of SnO2, and further comprises, by mass percentage, 0.5% or less of SnO2.

[0018] In another embodiment, the lithium zirconium aluminosilicate glass further comprises up to 0.5% CeO2 by weight.

[0019] More preferably, the lithium zirconium aluminosilicate glass contains 50% to 72% SiO2, 10% to 27% Al2O3, 0.1% to 10.0% B2O3, 2% to 10% Li2O, 4% to 15% Na2O, 0.1% to 5.0% ZrO2, 0 to 4% K2O, 4% or less by mass of MgO, 2% or less by mass of ZnO, 1% or less by mass of TiO2, 1% or less by mass of SnO2, and 0.5% or less by mass of CeO2. The total mass of Li2O, Na2O, and K2O is 9% or more, and the ratio of the mass of Li2O to the total mass of Li2O, Na2O, and K2O is (0.22 to 0.48):1.

[0020] In this embodiment, the lithium zirconium aluminosilicate glass does not contain P2O5 and Fe2O3. When P2O5 is not added to the lithium zirconium aluminosilicate glass, the turbidity of PB phase separation caused by the addition of P2O5 and B2O3 can be avoided, and the increase in haze (i.e., opacity) and the decrease in chemical stability of the glass can be avoided.

[0021] SiO2 (silicon dioxide) is an important oxide in glass formation and is an essential component for forming a glass skeleton. SiO2 can improve the strength and chemical stability of glass, and can give glass a high strain point and a low thermal expansion coefficient. In this embodiment, the mass percentage of SiO2 is preferably 50% to 72%, more preferably 55% to 67%, and most preferably 58% to 64%. If the mass percentage of SiO2 is less than 50%, the mesh structure of the glass body is poor, the mechanical properties are poor, and the weather resistance is poor. If the mass percentage of SiO2 exceeds 72%, the melting temperature of glass in the manufacturing process becomes high, the energy consumption increases, and defects such as bubbles and stones are likely to occur frequently. Furthermore, since the proportion of the silica-oxygen skeleton structure is relatively high and the gaps in the mesh are small, it has an adverse effect on chemical strengthening by ion exchange and affects the efficiency of chemical strengthening. Therefore, in this embodiment, the mass percentage of SiO2 is set to 50% to 72%.

[0022] Al2O3 (aluminum trioxide) is involved in the formation of the network and functions as a network former, and can reduce the tendency of glass to crystallize and improve the chemical stability, thermal stability, mechanical strength, and hardness of glass. In addition, Al2O3 is also an essential component for increasing the elastic modulus of drawn glass. However, the addition of Al2O3 increases the viscosity of glass. If the mass fraction of Al2O3 is too high, it becomes difficult to obtain glass with long material properties, and glass molding becomes difficult. In addition, the Al content in glass is 3+ tends to form an aluminum oxygen tetrahedron network [AlO4] that is much larger than a silicon oxygen tetrahedron [SiO4] network, leaving large gaps as channels for ion diffusion, so that a higher content of Al2O3 in glass promotes the movement and substitution rate of alkali metal ions. The higher the content of Al2O3, the larger the gaps in the skeleton network, which promotes ion exchange, but the thermal expansion coefficient does not decrease further because of its high content. On the contrary, the high-temperature viscosity of glass increases significantly, the melting temperature in the manufacturing process becomes too high, energy consumption increases, and the control of defects such as bubbles and stones is adversely affected. However, if the content of Al2O3 is low, the gaps in the network space become small, which adversely affects the movement of ions and seriously affects the efficiency of chemical strengthening. Therefore, in this embodiment, the mass fraction of Al2O3 is preferably 10% to 27%, more preferably 13% to 25%, and most preferably 16% to 22%.

[0023] B2O3 (boron oxide) is one of the important components of boroaluminosilicate glass, belongs to the oxide of the former, and can reduce the thermal expansion coefficient of aluminosilicate glass and improve the thermal stability and chemical stability of aluminosilicate glass. If the content of B2O3 is too high, boron will volatilize violently due to the viscosity reducing effect at high temperatures. In addition, if the content of B2O3 is too high, the forming temperature will be narrowed, and it will be difficult to precisely control the wall thickness and tube diameter during the process of stretching the boroaluminosilicate glass to form a tube. Furthermore, if the amount of B2O3 introduced is too high, the boroaluminosilicate glass expansion coefficient etc. will be increased conversely due to the increase in the borooxygen triangle [BO3], resulting in abnormal phenomena. If the content of B2O3 is too high, the ion exchange capacity of the glass will be greatly reduced. Therefore, in this embodiment, the mass percentage of B2O3 is preferably 0.1% to 10.0%, more preferably 0.5% to 4%, and most preferably 1% to 2%.

[0024] Li2O (lithium oxide) is an ideal flux and the main component of ion exchange. + The polarization properties of Li can effectively reduce the high-temperature viscosity at high temperatures. + Because of its small radius, Li2O can be filled into the air in the glass body to balance the free oxygen. Therefore, an appropriate amount of Li2O can greatly improve the mechanical strength, surface hardness, and chemical resistance of the glass body. In this embodiment, the mixed molten salt of NaNO3 and KNO3 is used in the strengthening process, so the Li in the glass can be easily filled into the air in the glass body to balance the free oxygen. + and Na in molten salt + By carrying out ion exchange with Li2O, the depth of the compressive stress layer can be increased in a short time, and the glass has better mechanical impact resistance. The mass percentage of Li2O is preferably 2% to 10%, more preferably 3% to 7%, and most preferably 4% to 6%. If the mass percentage of Li2O is less than 2%, it is basically difficult for the glass to obtain a higher stress layer depth, and if it exceeds 10%, the manufacturing cost of the glass is increased, the expansion coefficient of the glass is greatly increased, and the crystallization tendency of the glass is very high, and the possibility of defects such as stone formation in the glass is greatly increased.

[0025] Na2O (sodium oxide) is a network modifying oxide of boroaluminosilicate glass, and can supply free oxygen to break Si-O bonds, thereby reducing the viscosity and melting temperature of the aluminosilicate glass. If the content of Na2O is too high, the linear thermal expansion coefficient increases, the chemical stability decreases, and the amount of volatilization of Na2O increases, which may lead to non-uniform composition of the aluminosilicate glass. Alternatively, if the content of Na2O is too low, it will have an adverse effect on the melting and forming of glass, and will have an adverse effect on the achievement of the purpose of increasing the mechanical strength of glass by forming a compressive stress layer on the surface of glass through chemical exchange of Na ions and K ions. In this embodiment, the Na2O component plays a role of forming compressive stress on the glass surface by exchanging with K ions in the melt during tempering, and therefore directly affects the strength performance of glass. Therefore, in this embodiment, the mass percentage of Na2O is preferably 4% to 15%, more preferably 6% to 12%, and most preferably 8% to 10%.

[0026] K2O (potassium oxide) and Na2O are both alkali metal oxides and have similar functions in glass structure. Using a small amount of K2O instead of Na2O can exert a "mixed alkali effect" that improves a series of glass properties. K2O is a component used to improve melting properties and increase the ion exchange rate in chemical strengthening to obtain the required surface compressive stress and depth of the stress layer. If the content of K2O is too high, the weather resistance will decrease. In this embodiment, the inventor sets the mass percentage of K2O to 0-4% based on the analysis of the content of alkali metals in glass. The mass percentage of K2O is more preferably 0-3%, and most preferably 0-2%.

[0027] ZrO2 is mainly present in silicate glass in the form of cubic [ZrO8] coordination, and due to its large ionic radius, it belongs to the network modifier of the glass structure, and its solubility in glass is low, which causes a large increase in the viscosity of glass, so its addition amount should not exceed 5%. ZrO2 can improve the acid and alkali resistance and refractive index of glass. Therefore, in this embodiment, the mass percentage of ZrO2 is preferably 0.1% to 5.0%, more preferably 1% to 4%, and most preferably 3% to 4%.

[0028] MgO (magnesium oxide) is a kind of network modifying oxide, which is useful for lowering the melting point of glass, lowering the viscosity of glass at high temperatures, promoting the melting and clarification of glass, improving uniformity, and enhancing hydrolysis resistance. In addition, MgO can stabilize glass, improve the durability of glass, prevent glass crystallization, inhibit the movement of alkali metal ions in glass, and also has the function of improving the elastic modulus of glass. MgO can increase the stability of the glass network space at low temperatures and reduce the thermal expansion coefficient of glass to a certain extent, but since it has an inhibitory effect on ion exchange, in this embodiment, MgO is not an essential component and may be omitted. In this embodiment, the mass percentage of MgO is preferably 0 to 6%, more preferably 0 to 4%, and most preferably 0 to 2%. When the mass percentage of MgO exceeds 6%, Mg 2+ This significantly inhibits the ion exchange capacity of the glass and greatly reduces the depth of the compressive stress layer.

[0029] CaO (calcium oxide) relaxes and destroys the network formed by silicon-oxygen tetrahedrons [SiO4], improving the melting properties of glass at high temperatures and making glass less susceptible to devitrification. However, if the content is too high, it affects the weather resistance of the aluminosilicate glass and significantly inhibits the progress of ion exchange, so in this embodiment, CaO is not an essential component and may be omitted. The mass percentage of CaO is preferably 0 to 4%, more preferably 0 to 2%.

[0030] SrO (strontium oxide) is similar to calcium oxide and magnesium oxide, and can reduce the high-temperature viscosity of glass and promote melting, but due to its large ionic radius, SrO does not inhibit the exchange process of Li-Na-K ions in the glass structure, so a small amount of strontium oxide may replace part of calcium oxide and magnesium oxide. In this embodiment, the mass percentage of SrO is preferably 0 to 4%, more preferably 0 to 2%. In this embodiment, SrO may also be omitted.

[0031] ZnO (zinc oxide) belongs to divalent metal oxides and also has the function of alkaline earth metal oxide. In silicate glass system, adding some ZnO material can effectively reduce the melting temperature of glass, lower the glass transition temperature Tg, and at the same time improve the alkali resistance of glass substrate. In aluminosilicate glass body, Zn always exists in two ligands [ZnO6] and [ZnO4], and [ZnO4] increases with increasing alkali content, increasing the crystallization tendency of glass. In the present invention, some zinc oxide is used to replace calcium oxide and magnesium oxide, which can maintain the chemical stability of glass and promote the rapid progress of ion exchange. The mass fraction of ZnO is preferably 0-4%, more preferably 0-2%. In this embodiment, ZnO may also be omitted.

[0032] TiO2 has the same function as ZrO2, is a transition element, has a certain coloring power, exhibits yellow color, improves the chemical stability of glass, and can increase the color temperature of glass. Therefore, in this embodiment, the mass percentage of TiO2 is preferably 0 to 2%, more preferably 0 to 1%. In this embodiment, TiO2 is not an essential component and may be omitted.

[0033] Both SnO2 and CeO2 are often present in the glass body in various valence states, which can increase the UV resistance of the glass and prevent color changes caused by valence changes of coloring ions. In addition, when SnO2 and CeO2 are added alone or in combination, they can also improve the high-temperature defoaming ability of the glass body as a commonly used fining agent. In this embodiment, the mass percentage of SnO2 is preferably 0-1%, more preferably 0-0.5%, and the mass percentage of CeO2 is preferably 0-0.5%. In this embodiment, both SnO2 and CeO2 are not essential components and may be omitted.

[0034] By setting the total mass of Li2O, Na2O, and K2O to 9% or more, the following effects can be obtained. Alkali metals, as typical glass network modifiers, can significantly reduce the melting temperature of glass. Furthermore, in the present invention, alkali metal ions are the key to whether glass can be chemically strengthened to realize ion exchange so that a sufficient compressive stress layer can be obtained on the surface of the glass. As a result of comprehensive consideration, the total mass of Li2O, Na2O, and K2O must be 9% or more.

[0035] By setting the ratio of the mass of Li2O to the sum of the masses of Li2O, Na2O, and K2O to (0.22~0.48):1, the following effects can be obtained. In the present invention, alkali metals are the key to whether glass can achieve high-performance chemical strengthening, and they play different roles during the chemical strengthening process. A certain proportion of Li is required in the glass body to replace some of the Na ions and K ions in the tempering salt in the first step of chemical tempering. Due to the difference in ion volume, a compressive stress layer with a stress gradient is formed on the glass surface, making the depth of the stress layer relatively deep, so that the strength and toughness of the glass can be increased. Over the long-term test, Li2O accounts for more than 22% of the total alkali metal content and should not exceed 48%. In addition to the proportion of Li2O in the total alkali metals affecting the tempering performance, due to the small relative molecular weight of Li2O, at the same mass rate, Li2O has a larger mole number than Na2O and K2O, which can significantly reduce the melting temperature of the glass, which is not conducive to production control, and too much Li2O may cause glass crystallization. Therefore, the proportion of Li2O in the alkali metals must not exceed 48%.

[0036] By setting the total mass of ZrO2 and Al2O3 to be greater than 10%, the following effects can be obtained. In the present invention, ZrO2 and Al2O3 are important components that determine the speed and difficulty of the exchange of alkali metal ions during the chemical tempering process, and as network intermediates, they are partially involved in the glass network structure. Large molecule ZrO2 fills the gaps in the network and forms loose structural channels for alkali metal ion exchange, promoting ion exchange in the depth direction of the glass. Thus, high stress depth and high surface stress are formed. In addition, ZrO2 and Al2O3 can improve the chemical stability of the glass, so the total mass of ZrO2 and Al2O3 needs to be greater than or equal to 10%.

[0037] In some embodiments, the lithium zirconium aluminosilicate glass preferably comprises, by mass, 55%-67% SiO2, 13%-25% Al2O3, 0.5%-4% B2O3, 3%-7% Li2O, 6%-12% Na2O, 1%-4% ZrO2, and 0-3% K2O, where the sum of the masses of Li2O, Na2O, and K2O is 9% or more, the sum of the masses of ZrO2 and Al2O3 is greater than 16%, and the ratio of the mass of Li2O to the sum of the masses of Li2O, Na2O, and K2O is (0.27-0.41):1.

[0038] In this embodiment, the lithium zirconium aluminosilicate glass may further include at least one of MgO, CaO, SrO, ZnO, and TiO2. Specifically, the mass percentage of MgO is 6% or less, the mass percentage of CaO is 4% or less, the mass percentage of SrO is 4% or less, the mass percentage of ZnO is 4% or less, and the mass percentage of TiO2 is 2% or less.

[0039] Furthermore, the mass percentage of MgO is 4% or less, the mass percentage of CaO is 2% or less, the mass percentage of SrO is 2% or less, the mass percentage of ZnO is 2% or less, and the mass percentage of TiO2 is 1% or less.

[0040] In this embodiment, the lithium zirconium aluminosilicate glass may further include at least one of SnO2 and CeO2, and the mass percentage of SnO2 may be 1% or less. Further, the mass percentage of SnO2 may be 0.5% or less and the mass percentage of CeO2 may be 0.5% or less.

[0041] More preferably, in this embodiment, the lithium zirconium aluminosilicate glass contains 55%-67% SiO2, 13%-25% Al2O3, 0.5%-4% B2O3, 3%-7% Li2O, 6%-12% Na2O, 1%-4% ZrO2, 0-3% K2O, 4% or less by mass of MgO, 2% or less by mass of ZnO, 1% or less by mass of TiO2, 1% or less by mass of SnO2, and 0.5% or less by mass of CeO2. The sum of the masses of Li2O, Na2O, and K2O is 9% or more, the sum of the masses of ZrO2 and Al2O3 is more than 16%, and the ratio of the mass of Li2O to the sum of the masses of Li2O, Na2O, and K2O is (0.27-0.41):1.

[0042] In this embodiment, MgO, CaO, SrO, ZnO, TiO2, SnO2, and CeO2 may be omitted.

[0043] In another embodiment, more preferably, the lithium zirconium aluminosilicate glass comprises, by mass, 58%-64% SiO2, 16%-22% Al2O3, 1%-2% B2O3, 4%-6% Li2O, 8%-10% Na2O, 3%-4% ZrO2, and 0-2% K2O, where the sum of the masses of Li2O, Na2O, and K2O is 9% or more, the sum of the masses of ZrO2 and Al2O3 is greater than 19.5%, and the ratio of the mass of Li2O to the sum of the masses of Li2O, Na2O, and K2O is (0.29-0.38):1.

[0044] In this embodiment, the lithium zirconium aluminosilicate glass may further include at least one of MgO, CaO, SrO, ZnO, and TiO2. Specifically, the mass percentage of MgO is 6% or less, the mass percentage of CaO is 4% or less, the mass percentage of SrO is 4% or less, the mass percentage of ZnO is 4% or less, and the mass percentage of TiO2 is 2% or less.

[0045] Furthermore, the mass percentage of MgO is 4% or less, the mass percentage of CaO is 2% or less, the mass percentage of SrO is 2% or less, the mass percentage of ZnO is 2% or less, and the mass percentage of TiO2 is 1% or less.

[0046] Furthermore, in this embodiment, the lithium zirconium aluminosilicate glass may further include at least one of SnO2 and CeO2, where the mass percentage of SnO2 is 0.5% or less and the mass percentage of CeO2 is 0.5% or less.

[0047] More preferably, in this embodiment, the lithium zirconium aluminosilicate glass contains 58%-64% SiO2, 16%-22% Al2O3, 1%-2% B2O3, 4%-6% Li2O, 8%-10% Na2O, 3%-4% ZrO2, 0-2% K2O, 4% or less by mass of MgO, 2% or less by mass of ZnO, 1% or less by mass of TiO2, 1% or less by mass of SnO2, and 0.5% or less by mass of CeO2. The sum of the masses of Li2O, Na2O, and K2O is 9% or more, the sum of the masses of ZrO2 and Al2O3 is more than 19.5%, and the ratio of the mass of Li2O to the sum of the masses of Li2O, Na2O, and K2O is (0.29-0.38):1.

[0048] In this embodiment, MgO, ZnO, TiO2, SnO2, and CeO2 may be omitted.

[0049] The prior art discloses glass compositions containing non-zero and less than 1 mol% P2O5 and K2O, and the ratio of the mass of Li2O to the sum of the masses of B2O3, P2O5, SiO2, and Al2O3 is less than 0.074. In contrast, the lithium zirconium aluminosilicate glass in the embodiment of the present invention does not contain P2O5, so that the turbidity of PB phase separation caused by the addition of P2O5 and B2O3 can be avoided, and the increase in haze (i.e., opacity) can be avoided. In addition, the inclusion of P2O5 in the glass reduces the chemical stability of the glass, especially due to corrosion of the glass by water vapor and acidic liquids. Furthermore, in the embodiment of the present invention, the ratio of Li2O to the total molar amount of B2O3, P2O5, SiO2, and Al2O3 is generally higher than 0.074, and the amount of Li2O is generally higher than the amount of Na2O, so that the advantage of exchanging the Li ions in the glass body with the Na and K ions in the strengthening salts can be fully utilized. As a result, the lithium zirconium aluminosilicate glass in this embodiment has a surface stress value of more than 800 MPa and a depth of more than 130 μm, that is, the bending strength of the glass and the energy limit for withstanding impact are greatly increased.

[0050] Another technique discloses a thin lithium aluminum silicon glass, in which the central tension of the glass after tempering is less than 50Mpa, the surface compressive stress of the glass is 600Mpa-1200Mpa, and the bending strength of the glass can reach 500MPa. The depth of the stress layer of this glass should be less than 50μm. In contrast, the depth of the stress layer of the lithium zirconium aluminosilicate glass after tempering in this embodiment needs to be greater than 100μm, which is much larger than the depth of the stress layer of the tempered glass in the above technique.

[0051] In another conventional technology, the contents of B2O3 and ZrO2 are both low. In contrast, in this embodiment, the contents of B2O3 and ZrO2 are both 0.1% or more, which is beneficial to enhance the fracture toughness of glass in the subsequent processing of the glass substrate when they participate in the formation of the skeleton of the glass body structure. As a result, after tempering, the surface stress value is 800 MPa or more, and the compressive stress value at a depth of 100 μm is 55 MPa or more, improving the mechanical strength and drop resistance of the glass.

[0052] Therefore, in the conventional glass cover plate, rapid chemical tempering is possible, and a compressive stress layer of more than 600 MPa is formed on the glass surface, and the depth of the stress layer is generally more than 35 μm. In contrast, in the lithium aluminum-silicon glass with a special chemical tempering treatment, the depth of the stress layer can reach more than 100 μm, which can improve the mechanical strength, impact resistance, friction resistance, and resistance to sand and gravel falling on the ground of the glass. However, the strength of the conventional glass is not so high.

[0053] The lithium zirconium aluminosilicate glass has at least the following advantages:

[0054] (1) The above lithium zirconium aluminosilicate glass has a thermal expansion coefficient of 84.5 × 10 at 20℃ to 300℃. -7 ~94.9×10 -7 , melting temperature T2 is 1543°C~1638°C, glass transition temperature T g After the temperature is 497°C~586°C and special chemical tempering treatment, the surface compressive stress CS0 of the glass is greater than 800MPa, the compressive stress CS10 at a depth of 10μm from the glass surface is greater than 230MPa, the compressive stress CS30 at a depth of 30μm from the surface is greater than 140MPa, and the depth of the maximum stress layer due to ion exchange Dol0 is greater than 136μm.

[0055] (2) After being tempered, the lithium zirconium aluminosilicate glass has a bending strength of more than 700 MPa and a drop energy resistance of more than 0.4 J, so that it can be used as a protective glass for mobile phones, tablets, or other mobile smart devices.

[0056] Referring to FIG. 1, a method for producing lithium zirconium aluminosilicate glass according to one embodiment is a method for producing the above-mentioned lithium zirconium aluminosilicate glass, which specifically includes the following steps:

[0057] In step S110, the following raw materials are weighed out by mass: 50%-72% SiO2, 10%-27% Al2O3, 0.1%-10.0% B2O3, 2%-10% Li2O, 4%-15% Na2O, 0.1%-5.0% ZrO2, and 0-4% K2O, provided that the total mass of Li2O, Na2O, and K2O is 9% or more, the total mass of ZrO2 and Al2O3 is greater than 10%, and the ratio of the mass of Li2O to the total mass of Li2O, Na2O, and K2O is (0.22-0.48:1).

[0058] In step S120, the above-mentioned raw materials are mixed and melted to obtain a glass paste.

[0059] In one embodiment, in step S120, the temperature of melting is 1650° C. and the time of melting is 8 hours.

[0060] In step S130, the glass paste is subjected to a homogenization process.

[0061] In one embodiment, in step S130, the homogenization temperature is 1500° C., and the homogenization time is 1 hour.

[0062] In step S140, the glass paste is molded and then annealed to obtain lithium zirconium aluminosilicate glass.

[0063] Specifically, the step of forming the glass paste employs a casting molding method. In one embodiment, the homogenized glass paste is poured into an iron mold preheated to 450° C., and the glass paste is solidified.

[0064] In the above-mentioned method for producing lithium zirconium aluminosilicate glass, the glass may be obtained by a conventional flat glass production process, including but not limited to the float process, overflow downdraw process, Czochralski process, flat draw process, calendaring process, etc.

[0065] The tempered glass according to one embodiment is obtained by chemical tempering from the lithium zirconium aluminosilicate glass according to the above embodiment. Specifically, the lithium zirconium aluminosilicate glass contains, by mass percentage, 50% to 72% SiO2, 10% to 27% Al2O3, 0.1% to 10.0% B2O3, 2% to 10% Li2O, 4% to 15% Na2O, 0.1% to 5.0% ZrO2, and 0 to 4% K2O, the total mass of Li2O, Na2O, and K2O is 9% or more, the total mass of ZrO2 and Al2O3 is greater than 10%, and the ratio of the mass of Li2O to the total mass of Li2O, Na2O, and K2O is (0.22 to 0.48):1.

[0066] Referring to FIG. 2, a method for producing tempered glass according to an embodiment is the method for producing the tempered glass described above, and specifically includes the following steps.

[0067] In step S210, the lithium zirconium aluminosilicate glass is tempered for 2 to 6 hours in a molten mixture of NaNO3 and KNO3 with a mass ratio of 2:8 to 8:2 at a temperature of 390°C to 420°C.

[0068] Specifically, the lithium zirconium aluminosilicate glass is the lithium zirconium aluminosilicate glass of the above embodiment. Specifically, the lithium zirconium aluminosilicate glass contains, by mass percentage, 50% to 72% SiO2, 10% to 27% Al2O3, 0.1% to 10.0% B2O3, 2% to 10% Li2O, 4% to 15% Na2O, 0.1% to 5.0% ZrO2, and 0 to 4% K2O, the total mass of Li2O, Na2O, and K2O is 9% or more, the total mass of ZrO2 and Al2O3 is greater than 10%, and the ratio of the mass of Li2O to the total mass of Li2O, Na2O, and K2O is (0.22 to 0.48):1.

[0069] Furthermore, the mass ratio of the molten mixture in step S210 is 6:4 to 4:6. Next, in step S220, the lithium zirconium aluminosilicate glass is tempered for 2 to 4 hours in a molten mixture of NaNO3 and KNO3 in a mass ratio of 0.1:99.9 to 15:85 at a temperature of 380°C to 400°C to obtain tempered glass.

[0070] Lithium zirconium aluminosilicate glass is strengthened by a two-stage mixed salt method. The two-stage mixed salt method strengthens the glass and provides the following effects. The two-stage chemical tempering method can selectively exchange ions. The first stage is mainly the exchange of Li ions in the glass with Na ions and K ions in the tempering salt. The Na-Li exchange results in a compressive stress layer with a small compressive stress value and a large stress depth. In addition, the Li-K and Na-K exchanges can form large stresses to compensate for the low stress value in the high depth direction. In the second stage, the tempering salt with a high K ion content is used to temper the glass at a low temperature, so that the Na ions in the glass and the K ions in the tempering salt are rapidly exchanged to form a high-density stress layer with a shallow stress depth and a high compressive stress value on the glass surface. Finally, a composite stress layer is formed, which is characterized by a high stress layer of more than 700 MPa on the glass surface and a stress layer depth of more than 100 μm in the depth direction.

[0071] The effect of setting the mass ratio of sodium nitrate to potassium nitrate to 2:8-8:2 in step S210 is mainly to achieve chemical exchange between Na ions and Li ions in the glass to form a stress layer with sufficient depth. However, the radius of Na ions and Li ions is not so different, and the glass structure has enough space to accommodate the conversion of Na-Li ions, so the depth of the formed stress layer is deep but the stress value is low. By adding K with a large ionic radius to the tempering salt, Li-K exchange and Na-K exchange are realized in the stress direction, and some compressive stress values ​​are increased. Therefore, the mass ratio of sodium nitrate to potassium nitrate is set to 2:8-8:2 in the first stage. The effect of setting the mass ratio of sodium nitrate to potassium nitrate to 0.1:99.9-15:85 in step S220 is mainly to achieve exchange between Na ions in the glass and K ions in the tempering salt to form a stress layer with a high compressive stress value on the glass surface. This stress layer forms a composite compressive stress layer with the stress layer formed by the first stage tempering, improving the strength and toughness of the glass.

[0072] In the two-stage chemical tempering process, the temperature of the mixed melt in step S210 is usually 10°C to 20°C higher than the temperature of the mixed melt in step S220. Regarding the two elements of the tempering process, temperature and time, for the same tempering salt, the longer the treatment time and the higher the temperature, the deeper the stress layer formed, but the stress value will be greatly reduced. The purpose of the two-stage tempering in the present invention is different. The purpose of the first stage is to form a stress layer with sufficient depth (greater than 100 μm), and the higher the stress value, the better, so in the first stage, a higher temperature is selected, usually 390°C to 420°C, and the time is 2 hours to 6 hours. The purpose of the second stage is to form a high-stress stress layer of a certain depth (greater than 700 MPa), so in the second stage, a lower temperature and a shorter time are required, usually 380°C to 400C, and the time is 2 hours to 4 hours. The main reasons for not choosing long time are that the tempering cycle is too long, the efficiency and output are low, the cost is high, and it is not suitable for mass production.

[0073] The tempered glass obtained by tempering the lithium zirconium aluminosilicate glass by the above method has a bending strength of 700 MPa or more and can withstand a drop energy of 0.4 J or more, so that it can effectively avoid or reduce breakage of the glass of the screen or cover plate of a smart device such as a mobile phone caused by an accidental drop to the ground, and can be used as a protective glass for mobile smart devices such as mobile phones and tablets.

[0074] In one embodiment, a display component includes the lithium zirconium aluminosilicate glass, the tempered glass, or the tempered glass produced by the tempered glass production method. The display component includes a smart mobile device, a digital camera, etc. The lithium zirconium aluminosilicate glass or the tempered glass has high strength and can be used as a protective glass to prevent damage to a smart mobile device or the like due to an accidental drop.

[0075] Below are some specific examples.

[0076] The manufacturing process of the lithium zirconium aluminosilicate glass of Examples 1 to 21 is specifically as follows.

[0077] The raw materials were mixed completely and uniformly according to the compositions (mass ratios) of Examples 1 to 21 shown in Tables 1 to 3 below, and then melted in a platinum crucible at 1650°C for 8 hours while stirring with a platinum stirring paddle. After the stirring paddle was removed, the melt was cooled to 1500°C and kept at room temperature for 1 hour to homogenize. Next, the melt was poured into an iron mold to form a glass block of about 80 mm x 160 mm in size. Before pouring, the mold was preheated to 450°C, and immediately after hardening, the glass block was transferred to an annealing furnace for annealing (annealing temperature was 590°C) and kept at room temperature for 2 hours. After that, it was cooled to 140°C for 6 hours, and then naturally cooled to obtain lithium zirconium aluminosilicate glass.

[0078] The strengthening process of the lithium zirconium aluminosilicate glasses of Examples 1 to 7 is specifically as follows.

[0079] The lithium zirconium aluminosilicate glasses obtained in Examples 1 to 7 above were processed into double-sided polished glass plates measuring 50 mm x 50 mm x 0.7 mm. The glass plates were tempered in a 395°C molten mixture of NaNO3:KNO3 = 1:1 (mass ratio) for 4 hours, and then transferred to a 380°C molten mixture of NaNO3:KNO3 = 8:92 (mass ratio) and tempered for 2 hours to obtain tempered glass.

[0080] The strengthening process of the lithium zirconium aluminosilicate glasses of Examples 8 to 14 is specifically as follows.

[0081] The lithium zirconium aluminosilicate glasses obtained in Examples 8 to 14 above were processed into double-sided polished glass plates measuring 50 mm x 50 mm x 0.7 mm. The glass plates were tempered for 2 hours in a molten mixture of NaNO3:KNO3 = 8:2 (mass ratio) at 420°C, and then transferred to a molten mixture of NaNO3:KNO3 = 15:85 (mass ratio) at 400°C and tempered for 2 hours to obtain tempered glass.

[0082] The strengthening process of the lithium zirconium aluminosilicate glasses of Examples 15 to 21 is specifically as follows.

[0083] The lithium zirconium aluminosilicate glasses obtained in Examples 15 to 21 above were processed into double-sided polished glass plates of 50 mm × 50 mm × 0.7 mm. The glass plates were tempered in a molten mixture of NaNO3:KNO3 = 2:8 (mass ratio) at 405°C for 6 hours, and then transferred to a molten mixture of NaNO3:KNO3 = 0.1:99.9 (mass ratio) at 390°C and tempered for 4 hours to obtain tempered glass.

[0084] The manufacturing processes for the lithium zirconium aluminosilicate glasses of Comparative Examples 1 to 13 are similar to the manufacturing processes for the lithium zirconium aluminosilicate glasses of Examples 1 to 21, except that the compositions of the raw materials are shown in Tables 4 and 5.

[0085] The strengthening process of the lithium zirconium aluminosilicate glasses of Comparative Examples 1 to 10 was similar to the strengthening process of the lithium zirconium aluminosilicate glasses of Examples 1 to 7, and therefore a repeated explanation will be omitted.

[0086] The strengthening process of the lithium zirconium aluminosilicate glass of Comparative Example 11 is specifically as follows.

[0087] The lithium zirconium aluminosilicate glass obtained in Comparative Example 11 was processed into a double-sided polished glass plate of 50 mm × 50 mm × 0.7 mm. The glass plate was tempered in a molten mixture of NaNO3:KNO3 = 1:1 (mass ratio) at 395 ° C for 6 hours to obtain tempered glass.

[0088] The strengthening process of the lithium zirconium aluminosilicate glass of Comparative Example 12 is specifically as follows.

[0089] The lithium zirconium aluminosilicate glass obtained in Comparative Example 12 was processed into a double-sided polished glass plate of 50 mm × 50 mm × 0.7 mm. The glass plate was tempered in a molten mixture of NaNO3:KNO3 = 8:92 (mass ratio) at 380 °C for 6 hours to obtain a tempered glass.

[0090] The strengthening process of the lithium zirconium aluminosilicate glass of Comparative Example 13 is specifically as follows.

[0091] The lithium zirconium aluminosilicate glass obtained in Comparative Example 13 above was processed into a double-sided polished glass plate of 50 mm x 50 mm x 0.7 mm. The glass plate was tempered in a 395°C NaNO3:KNO3 = 8:92 (mass ratio) molten mixture for 4 hours, and then transferred to a 380°C NaNO3:KNO3 = 1:1 (mass ratio) molten mixture for 2 hours to obtain a tempered glass. Test

[0092] The lithium zirconium aluminosilicate glasses obtained in the above Examples 1 to 21 and Comparative Examples 1 to 13 were all processed into glass samples of φ5 mm × 50 mm. The thermal expansion curves were measured at a heating rate of 4°C / min using a thermal dilatometer (NETZSCH-DIL 402 PC). The strain point temperatures T g , expansion softening temperature T s The thermal expansion coefficients CTE in the range of 20°C to 300°C were measured using the built-in software and are recorded in Tables 1 to 5.

[0093] The high-temperature viscosity of each of the lithium zirconium aluminosilicate glasses obtained in Examples 1 to 21 and Comparative Examples 1 to 13 was measured using 250 g of each glass high-temperature viscometer (ORTON, RSV-1600). The temperature at which the viscosity was 102 dPa.S was defined as the glass melting temperature T2, and the temperatures at which the viscosity was 103 dPa.S, 104 dPa.S, and 105 dPa.S were defined as T3, T4, and T5, respectively. These values ​​are recorded in Tables 1 to 5.

[0094] For tempered glass, the surface stress value CS0, the compressive stress value CS10 at a depth of 10 μm, the compressive stress value CS30 at a depth of 30 μm, the compressive stress value CS100 at a depth of 100 μm, the maximum stress layer depth Dol0 at the maximum stress value, and the stress layer depth Dol600 at 600 MPa were measured using stress testers FSM6000 and SLP1000 (Orihara Co., Ltd., Japan), and the results are recorded in Tables 1 to 5.

[0095] The lithium zirconium aluminosilicate glasses obtained in Examples 1 to 21 and Comparative Examples 1 to 10 were cut into glass plates of 70 mm x 140 mm x 0.7 mm by an STX-1203 wire cutter (Shenyang Kejing Co., Ltd.). The glass plates were thinned and polished by an HD-640-5L double-sided grinding and polishing machine (Shenzhen Haidu Co., Ltd.), and then edged by a computer numerical control (CNC). After cleaning, the glasses were tempered in a 395°C mixed melt of NaNO3:KNO3 = 1:1 (mass ratio) for 4 hours, and then transferred to a 380°C mixed melt of NaNO3:KNO3 = 8:92 (mass ratio) for 2 hours to obtain tempered glass substrates. The four-point bending strength was measured by a PT-307A universal testing machine (Precise Test Co., Ltd.), and the drop energy that the center of the glass substrate could withstand was measured by a PT-706 drop tester (Precise Test Co., Ltd.). The center was hit with a 64g solid steel ball, and if the center did not break after three hits, the height Hmm was recorded. The fall energy was calculated as C = 64 × H / 10000 (unit: J) and recorded in Tables 1 to 5.

[0096] The lithium zirconium aluminosilicate glasses obtained in Comparative Examples 11 to 13 were cut into glass plates of 70 mm x 140 mm x 0.7 mm by an STX-1203 wire cutter (Shenyang Kejing Co., Ltd.). The glass plates were thinned and polished by an HD-640-5L double-sided grinding and polishing machine (Shenzhen Haidu Co., Ltd.), and then edged by a computer numerical control (CNC). After cleaning, tempering treatment was performed according to the tempering treatment method of Comparative Examples 11 to 13 described above to obtain tempered glass substrates. The four-point bending strength was measured using a PT-307A universal testing machine (Precise Test Co., Ltd.), and the drop energy that the center of the glass substrate could withstand was measured using a PT-706 drop tester (Precise Test Co., Ltd.). The center was hit with a 64g solid steel ball, and if the center did not break after three hits, the height Hmm was recorded. The drop energy was calculated as C = 64 x H / 10000 (unit: J) and recorded in Table 5.

[0097] The lithium zirconium aluminosilicate glasses of Examples 1 to 7 shown in Table 1 contain, by mass, 50% to 72% SiO2, 10% to 27% Al2O3, 0.1% to 10.0% B2O3, 2% to 10% Li2O, 4% to 15% Na2O, 0.1% to 5.0% ZrO2, 0 to 4% K2O, 0 to 6% MgO, 0 to 4% CaO, 0 to 4% SrO, 0 to 4% ZnO, 0 to 2% TiO2, 0 to 1% SnO2, and 0 to 0.5% CeO2. The sum of the masses of Li2O, Na2O, and K2O is 9% or more, the sum of the masses of ZrO2 and Al2O3 is more than 10%, and the ratio of the mass of Li2O to the sum of the masses of Li2O, Na2O, and K2O is (0.22-0.48:1).

[0098] Regarding the lithium zirconium aluminosilicate glasses obtained in the above Examples 1 to 7, the lithium zirconium aluminosilicate glasses having the above compositional characteristics have a thermal expansion coefficient of 84.5×10 at 20° C. to 300° C. -7 ~94.9×10 -7 , melting temperature T2 is 1543°C~1638°C, glass transition temperature T g It was found that the temperature was 497°C to 586°C. The tempered glass obtained by tempering the lithium zirconium aluminosilicate glass obtained in Examples 1 to 7 in a mixed melt of NaNO3:KNO3 = 1:1 (mass ratio) at 395°C for 4 hours, then transferring to a mixed melt of NaNO3:KNO3 = 8:92 (mass ratio) at 380°C and tempering for 2 hours has a surface compressive stress CS0 of more than 800MPa, a compressive stress CS10 at a depth of 10μm from the glass surface still being 230MPa or more, a compressive stress CS30 at a depth of 30μm from the glass surface being 140MPa or more, and a stress depth Dol0 at which the composite compressive stress due to ion exchange drops to 0MPa (detection limit of the instrument) exceeds 136μm. The tempered glass has a bending strength of more than 740MPa and can withstand a drop energy of more than 0.32J.

[0099] [Table 1] Note: CS0 is the surface stress value, CS10 is the compressive stress value at a depth of 10 μm, CS30 is the compressive stress value at a depth of 30 μm, CS100 is the compressive stress value at a depth of 100 μm, Dol0 is the maximum stress layer depth, and Dol600 is the stress layer depth at 600 MPa.

[0100] A preferred composition ratio of the lithium zirconium aluminosilicate glass is shown in Table 2. The lithium zirconium aluminosilicate glasses of Examples 8 to 14 contain, by mass percentage, 55% to 67% SiO2, 13% to 25% Al2O3, 0.5% to 4% B2O3, 3% to 7% Li2O, 6% to 12% Na2O, 1% to 4% ZrO2, 0 to 3% K2O, 0 to 4% MgO, 0 to 2% CaO, 0 to 2% SrO, 0 to 2% ZnO, 0 to 1% TiO2, 0 to 0.5% SnO2, and 0 to 0.5% CeO2. The sum of the masses of Li2O, Na2O, and K2O is 9% or more, the sum of the masses of ZrO2 and Al2O3 is more than 16%, and the ratio of the mass of Li2O to the sum of the masses of Li2O, Na2O, and K2O is (0.27~0.41):1.

[0101] Regarding the lithium zirconium aluminosilicate glasses obtained in the above Examples 8 to 14, the lithium zirconium aluminosilicate glasses having the above compositional characteristics have a thermal expansion coefficient of 84.3 × 10 at 20 ° C to 300 ° C. -7 ~91.4×10 -7 , melting temperature T2 is 1581°C~1613°C, glass transition temperature T gIt was found that the temperature was 503°C to 558°C. The lithium zirconium aluminosilicate glass obtained in Examples 8 to 14 was tempered for 2 hours in a mixed melt of NaNO3:KNO3 = 8:2 (mass ratio) at 420°C, and then transferred to a mixed melt of NaNO3:KNO3 = 15:85 (mass ratio) at 400°C and tempered for 2 hours to obtain a tempered glass, which has a surface compressive stress CS0 of more than 900MPa, a compressive stress CS10 at a depth of 10μm from the glass surface that is still 275MPa or more, a compressive stress CS30 at a depth of 30μm from the glass surface that is 145MPa or more, and a stress depth Dol0 at which the composite compressive stress due to ion exchange drops to 0MPa (detection limit of the instrument) exceeds 145μm. The tempered glass has a bending strength of more than 810MPa and can withstand a drop energy of more than 0.48J.

[0102] [Table 2]

[0103] More preferred composition ratios of the lithium zirconium aluminosilicate glass are shown in Table 3. The lithium zirconium aluminosilicate glass of Examples 15 to 21 contains, by mass percentage, 58% to 64% SiO2, 16% to 22% Al2O3, 1% to 2% B2O3, 4% to 6% Li2O, 8% to 10% Na2O, 3% to 4% ZrO2, 0 to 2% K2O, 0 to 2% MgO, 0 to 2% ZnO, 0 to 0.5% SnO2, and 0 to 0.5% CeO2. The total mass of Li2O, Na2O, and K2O is 12% or more, the total mass of ZrO2 and Al2O3 exceeds 19.5%, and the ratio of the mass of Li2O to the total mass of Li2O, Na2O, and K2O is (0.29 to 0.38):1.

[0104] Regarding the lithium zirconium aluminosilicate glasses obtained in the above Examples 15 to 21, the lithium zirconium aluminosilicate glasses having the above compositional characteristics have a thermal expansion coefficient of 82.9 × 10 at 20 ° C to 300 ° C. -7 ~89.8×10 -7, melting temperature T2 is 1586°C~1612°C, glass transition temperature T g It was found that the temperature was 505°C to 546°C. The lithium zirconium aluminosilicate glass obtained in Examples 15 to 21 was tempered in a mixed melt of NaNO3:KNO3 = 2:8 (mass ratio) at 405°C for 6 hours, and then transferred to a mixed melt of NaNO3:KNO3 = 0.1:99.9 (mass ratio) at 390°C and tempered for 4 hours to obtain tempered glass, which has a surface compressive stress CS0 of more than 915MPa, a compressive stress CS10 at a depth of 10μm from the glass surface that is still 300MPa or more, a compressive stress CS30 at a depth of 30μm from the glass surface that is 160MPa or more, and a stress depth Dol0 at which the composite compressive stress due to ion exchange drops to 0MPa (detection limit of the instrument) exceeds 150μm. The tempered glass has a bending strength of more than 820MPa and can withstand a drop energy of more than 0.48J.

[0105] [Table 3]

[0106] The compositions and performance data of the lithium zirconium aluminosilicate glasses of Comparative Examples 1 to 7 are shown in Table 4 below. As can be seen from Table 4, in Comparative Example 1, the total content of alkali metals is less than 9%, and the melting temperature T2 is as high as 1652°C, which is a temperature that cannot be mass-produced in an actual glass furnace, especially a float furnace. In general, the melting temperature T2 needs to be controlled to 1640°C or lower. As a result of such a high melting temperature, not only does the consumption of energy such as natural gas and electric energy increase, but the life of the furnace, refractory bricks, and related equipment also shortens, and the costs also increase. In addition, it is very difficult to control it at the molding stage.

[0107] In Comparative Example 2, since it contains 0% Li2O, only a small amount of Na-K exchange can be realized in the first stage tempering, but it cannot form Li-Na exchange to form a high stress layer depth. Therefore, its Dol0 (μm) is 34.8 μm, CS30 (MPa) is 24 MPa, and CS100 (MPa) is 0 MPa. Therefore, its bending strength is 608 MPa, and it can withstand a drop energy of 0.24 J, which is much lower than that of Li-containing aluminosilicate glass.

[0108] In Comparative Example 3, Na2O was not included, and Li2O / (Li2O+Na2O+K2O) was 0.9, so the number of moles of Li2O increased significantly, and the molar content was close to 20%, causing the melting temperature of the glass to drop sharply and making it difficult to control the float forming. In addition, the increase in the Li2O content caused the glass to devitrify, and when turbidity occurred, the transmittance decreased, and the bending strength and drop energy resistance also decreased.

[0109] In Comparative Example 4, the content of Li2O is 2.90%, the content of Na2O is 10.10%, and Li2O / (Li2O+Na2O+K2O) is 0.2, which is less than 0.22. As a result, after the glass is chemically tempered by two-stage tempering, its Dol0 is 98 μm, which is much lower than that of the examples of the present invention. Both its final bending strength and drop energy resistance are reduced, and the drop energy resistance is reduced to 0.24 J.

[0110] In Comparative Example 5, the Li2O content was 6.60%, the K2O content was 1.40%, and Li2O / (Li2O+Na2O+K2O) was 0.55, which is greater than 0.48. The CSO (MPa) of the tempered glass was 668 MPa, which was less than 700 MPa, and therefore the bending strength and drop strength of the glass were reduced. In addition, a small amount of devitrification occurred in the glass body, resulting in a reduction in its bending strength and a reduction in the drop energy it could withstand to 0.200 J.

[0111] In Comparative Example 6, the content of Al2O3 is 9.00%, which is less than 10%, the content of Al2O3+ZrO2 is 9.50%, which is less than 10%, and the content of B2O3 is 4.00%. The reduction in the content of Al2O3+ZrO2, especially Al2O3, seriously affected the glass structure. Since Al2O3 is involved in the structure as a glass intermediate, when its content is too low, the tempering performance of the glass body, especially the second stage Na-K exchange, is reduced. As a result, the stress layer and the depth of the stress layer on the glass surface are reduced, and the strength, especially the bending strength and drop strength, are also reduced.

[0112] In Comparative Example 7, ZrO2 was not included and the content of Al2O3 was 10.1%. Compared with Example 7, the gaps in the glass structure were not filled with ZrO2, so a sufficiently stable glass structure space could not be formed. When glass is subjected to an external force, the gaps in the structure contain ions of large electric field strength ZrO2 to offset part of the external stress. 4+ The absence of this material makes it easier for stress concentrations to occur that can cause glass products to break, reducing the bending strength and drop energy of the glass.

[0113] [Table 4]

[0114] The compositions and performance data of the lithium zirconium aluminosilicate glasses of Comparative Examples 8 to 13 are shown in Table 5 below. As can be seen from Table 5, Comparative Example 8 contains 1% P2O5 and 26% Al2O3, and compared with Example 1, the compressive stress value after tempering decreased, the depth of the stress layer increased slightly, and the tensile stress value at the center of the glass increased. As a result, both the bending strength of the glass and the drop impact energy it can withstand decreased to a certain extent.

[0115] In Comparative Example 9, B2O3 was not included, and the SiO2 content was 54.50%, and compared with Example 2, both the stress value and stress depth after tempering increased slightly. However, since boron oxide, mainly boron oxygen triangles and boron oxygen tetrahedra, are not involved in the glass network structure, when the glass is subjected to external impact, there is no buffer structure to offset the stress in this area, which makes it easy to cause stress concentration and reduces various strength properties. As is clear from Comparative Example 9, the tempering performance was improved, but both the bending strength of the glass and the impact energy it can withstand were reduced.

[0116] In Comparative Example 10, the content of Fe2O3 is 0.10%, and the content of SiO2 is 57.90%. Compared with Example 3, the thermal performance and the difficulty of glass melting are almost the same, and the stress value and stress depth after two-stage tempering are also basically similar. The bending strength and drop energy resistance are slightly reduced, but the color is obviously yellow, which is not suitable for industrial applications such as display covers, and should be avoided as much as possible.

[0117] In the strengthening step of Comparative Example 11, only the first strengthening step was carried out. Compared with Example 4, the tempering process did not allow Na-K ion exchange and a large amount of Li-K ion exchange, so there was only Li-Na exchange and a small amount of Li-K exchange on the surface, and the stress value of the glass surface was only 386 MPa. Since the second-stage exchange was not performed, the total stress depth Dol0 (μm) was also 20 μm to 30 μm lower than that of Example 4, the bending strength of the glass was only 524 MPa, and the drop energy it could withstand was less than 0.2 J.

[0118] In the strengthening step of Comparative Example 12, only the second strengthening step was carried out. Compared with Example 5, the tempering process could not carry out Li-Na ion exchange, so only Li-K exchange and Na-K exchange were carried out, and the compressive stress value of the glass surface was high, but the stress depth was only about 5.4 μm, and its CS10, CS30, and CS100 were all 0, and Dol0 (μm) was only 5.4 μm, which was much lower than the average level of over 100 microns caused by the secondary strengthening. As a result, the bending strength of the glass was only 489 MPa, and the drop energy it could withstand was less than 0.2 J.

[0119] In the strengthening step of Comparative Example 13, the ratio of sodium nitrate and potassium nitrate is not within the range claimed in this specification, so that the Li-Na exchange and Na-K and part of Li-K exchange in the first stage tempering during the tempering process are not optimal, and the main Na-K ion exchange in the second stage tempering is also at a relatively low level, and its various tempering data are much lower than that of Example 6, which directly leads to a significant decrease in its bending strength and drop energy resistance.

[0120] [Table 5]

[0121] As can be seen from the above experimental results, the tempered glass obtained by subjecting the lithium zirconium aluminosilicate glass produced in Examples 1 to 21 to a two-stage tempering treatment had a surface compressive stress CS0 of more than 800 MPa, a compressive stress CS10 at a depth of 10 μm from the glass surface that was still 230 MPa or more, and a compressive stress CS30 at a depth of 30 μm from the glass surface that was 140 MPa or more, a stress depth Dol0 at which the composite compressive stress due to ion exchange decreased to 0 MPa (detection limit of the instrument) was more than 136 μm, a bending strength was more than 700 MPa, and a drop energy resistance exceeded 0.4 J.

[0122] The technical features of the above-mentioned embodiments can be combined in any combination. For the sake of brevity, all combinations of the technical features in the above-mentioned embodiments are not described, but the combinations of these technical features should be considered within the scope described in this specification unless they are inconsistent.

[0123] The above examples merely show some embodiments of the present invention, and the description is specific and detailed, but should not be construed as limiting the scope of the claims. However, those skilled in the art can make some modifications and improvements without departing from the spirit of the present invention, and all of these are within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be in accordance with the scope of the claims.

Claims

1. A lithium zirconium aluminosilicate glass comprising, by weight, 50% to 72% SiO 2 , 10% to 27% Al 2 O 3 , 0.1% to 10.0% B 2 O 3 , 2%~10%のLi 2 O、 4% to 15% Na 2 O. 0.1% to 5.0% ZrO 2 , 0-4% K 2 O, and TiO2% or less 2 Including, However, the lithium zirconium aluminosilicate glass does not contain CaO, The Li 2 O, the Na 2 O, and the K 2 The total mass of O is 9% or more, and the Li 2 The mass of O and the Li 2 O, the Na 2 O, and the K 2 The ratio of the mass of O to the total mass of O is (0.22 to 0.48):1, A lithium zirconium aluminosilicate glass, wherein the sum of the masses of said ZrO 2 and said Al 2 O 3 exceeds 10%, and the ratio of the mass of said Li 2 O to the sum of the masses of said Li 2 O, said Na 2 O, and said K 2 O is (0.27-0.41):

1.

2. The Li 2 O, the Na 2 O, and the K 2 The total mass of O is 12% or more, and the ZrO 2 and the Al 2 O 3 The total mass of Li is greater than 19.5%, 2 The mass of O and the Li 2 O, the Na 2 O, and the K 2 2. The lithium zirconium aluminosilicate glass according to claim 1, characterized in that the ratio of the mass of O to the total mass of O is (0.29-0.38):

1.

3. The ZrO 2 The mass percentage of Al is 1% to 4%. 2 O 3 The lithium zirconium aluminosilicate glass according to claim 1, characterized in that the mass fraction of is 13% to 25%.

4. The ZrO 2 The mass percentage of Al is 3% to 4%. 2 O 3 The lithium zirconium aluminosilicate glass according to claim 3, characterized in that the mass percentage of is 16% to 22%.

5. The Li 2 The mass percentage of O is 3% to 7%, and the Na 2 The mass ratio of O is 6% to 12%, 2 2. The lithium zirconium aluminosilicate glass according to claim 1, wherein the mass percentage of O is 0 to 3%.

6. The Li 2 The mass percentage of O is 4% to 6%, and the Na 2 The mass ratio of O is 8% to 10%, 2 6. The lithium zirconium aluminosilicate glass according to claim 5, characterized in that the mass percentage of O is 0 to 2%.

7. The lithium zirconium aluminosilicate glass has a mass percentage of 55% to 67% SiO 2 , 13% to 25% Al 2 O 3 , 0.5% to 4% B 2 O 3 , 3% to 7% Li 2 O, 6% to 12% Na 2 O, 1% to 4% ZrO 2 , and 0-3% K 2 O, and the ZrO 2 and the Al 2 O 3 The total mass of Li is greater than 16%, 2 O, the Li 2 The mass of O and the Na 2 O, and the K 2 2. The lithium zirconium aluminosilicate glass according to claim 1, characterized in that the ratio of the mass of O to the total mass of O is (0.27-0.41):

1.

8. The lithium zirconium aluminosilicate glass has a mass percentage of 58% to 64% SiO 2 , 16% to 22% Al 2 O 3 , 1% to 2% B 2 O 3 , 4% to 6% Li 2 O, 8% to 10% Na 2 O, 3% to 4% ZrO 2 , and 0-2% K 2 O, and the Li 2 O, the Na 2 O, and the K 2 The total mass of O is 12% or more, and the ZrO 2 and the Al 2 O 3 The total mass of Li is greater than 19.5%, 2 The mass of O and the Li 2 O, the Na 2 O, and the K 2 8. The lithium zirconium aluminosilicate glass according to claim 7, characterized in that the ratio of the mass of O to the total mass of O is (0.29-0.38):

1.

9. The lithium zirconium aluminosilicate glass according to any one of claims 1 to 8, further comprising at least one of MgO having a mass percentage of 6% or less, SrO having a mass percentage of 4% or less, and ZnO having a mass percentage of 4% or less.

10. The lithium zirconium aluminosilicate glass according to any one of claims 1 to 8, further comprising at least one of MgO having a mass percentage of 4% or less, SrO having a mass percentage of 2% or less, and ZnO having a mass percentage of 2% or less.

11. The lithium zirconium aluminosilicate glass according to any one of claims 1 to 8, further comprising MgO in a mass fraction of 2% or less.

12. The lithium zirconium aluminosilicate glass has a mass fraction of 1% or less of SnO 2 and CeO having a mass fraction of 0.5% or less 2 The lithium zirconium aluminosilicate glass according to any one of claims 1 to 8, further comprising:

13. The lithium zirconium aluminosilicate glass further comprises 4% by mass or less of MgO, 2% by mass or less of ZnO, 0.5% by mass or less of SnO 2 and CeO having a mass fraction of 0.5% or less 2 The lithium zirconium aluminosilicate glass according to any one of claims 1 to 8, comprising:

14. Tempered glass obtained by chemical strengthening the lithium zirconium aluminosilicate glass according to any one of claims 1 to 13.

15. 15. The tempered glass of claim 14, wherein the tempered glass has a bending strength of greater than 700 MPa and a drop energy resistance of greater than 0.4 J.

16. The lithium zirconium aluminosilicate glass according to any one of claims 1 to 13 is first treated with NaNO at a temperature of 390°C to 420°C and a mass ratio of 2:8 to 8:

2. 3 and KNO 3 Then, the mixture is tempered for 2 to 6 hours in a melt of NaNO at a temperature of 380°C to 400°C and in a mass ratio of 0.1:99.9 to 15:

85. 3 and KNO 3 and performing a tempering treatment in the molten mixture of the above for 2 to 4 hours to obtain tempered glass.

17. First, NaNO with a temperature of 390°C to 420°C and a mass ratio of 2:8 to 8:2 3 and KNO 3 In the step of performing tempering treatment for 2 to 6 hours in a mixed melt of NaNO 3 and KNO 3 The method for producing tempered glass according to claim 16, wherein the mass ratio of the above is 6:4 to 4:

6.

18. First, NaNO with a temperature of 390°C to 420°C and a mass ratio of 2:8 to 8:2 3 and KNO 3 The temperature in the step of tempering for 2 to 6 hours in the mixed melt of NaNO at a temperature of 380° C. to 400° C. and a mass ratio of NaNO at 0.1:99.9 to 15:85 is then 3 and KNO 3 18. The method for producing tempered glass according to claim 16, wherein the temperature is about 10° C. to 20° C. higher than the temperature in the step of performing tempering treatment in the molten mixture of the above for 2 to 4 hours.

19. A display component comprising the lithium zirconium aluminosilicate glass according to any one of claims 1 to 13, or the tempered glass according to any one of claims 14 to 15, or the tempered glass produced by the method for producing tempered glass according to any one of claims 16 to 18.

Citation Information

Patent Citations

  • Cover glass for display

    JP2013028506A

  • Chemically strengthened glass

    JP2013520388A

  • Flexible ultra-thin chemically strengthened glass

    JP2016508954A

  • Ultra-thin chemically strengthened glass article and method for manufacturing such glass article

    JP2017529304A